Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Review: 29

Answer

$-\frac{1}{3}$

Work Step by Step

$(-27)^{-\frac{1}{3}}=\frac{1}{(-27)^{\frac{1}{3}}}=\frac{1}{\sqrt[3] (-27)}=\frac{1}{(-3)}=-\frac{1}{3}$ We know that $\sqrt[3] (-27)=-3$, because $(-3)^{3}=-3\times-3\times-3=-27$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.